2020
DOI: 10.1016/j.purol.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Recommandations CCAFU sur la prise en charge des cancers de l’appareil urogénital en période d’épidémie au Coronavirus COVID-19

Abstract: Pages 11 2 A. Méjean et al. Résultats. -La prise en charge médicale et chirurgicale des patients atteints de cancers de l'appareil urinaire et génital masculin doit être adaptée en modifiant les modalités de consultation, en priorisant les interventions en fonction du pronostic intrinsèque des cancers en tenant compte des comorbidités du patient. La protection des urologues vis-à-vis du COVID-19 doit être prise en considération. Conclusion. -Le CCAFU émet un avis d'experts quant aux mesures à prendre pour adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
53
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 24 publications
0
53
0
4
Order By: Relevance
“…Owing to the recent emergence and rapid spread of SARS coronavirus 2, many national health authorities are recommending cancellation of scheduled elective surgeries and office visits [1][2][3][4][5]. The objectives are to increase the availability of inpatient and intensive care unit beds, to permit internal redeployment of medical staff and nurses, and to avoid overwhelming the health care systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the recent emergence and rapid spread of SARS coronavirus 2, many national health authorities are recommending cancellation of scheduled elective surgeries and office visits [1][2][3][4][5]. The objectives are to increase the availability of inpatient and intensive care unit beds, to permit internal redeployment of medical staff and nurses, and to avoid overwhelming the health care systems.…”
mentioning
confidence: 99%
“…In the field of urological oncology, national and international guidance have recently provided valuable information for adapting patient care during the current pandemic [3,5]. Life-threatening or rapidly progressing malignant diseases (eg, muscle-invasive bladder cancer and testicular tumours) have been set as surgical priorities for which the usual standard of care should be maintained.…”
mentioning
confidence: 99%
“…8 Also, intraperitoneal CO 2 should be extracted using the active smoke evacuation mode. 9 Moreover, some authors have suggested that use of laparoscopy should be reserved for COVID-19 negative patients, except for cases in which the risks of laparotomy far outweigh the risks of laparoscopy. 10 For endoscopic surgery in suspected or confirmed COVID-19 patients, complete protection against infection is recommended.…”
mentioning
confidence: 99%
“…10 For endoscopic surgery in suspected or confirmed COVID-19 patients, complete protection against infection is recommended. 2,9 The same precaution needs to be taken when the anus is accessible in the operating field. 9 Healthcare workers in contact with such patients must also wear a double pair of gloves and long shoe covers.…”
mentioning
confidence: 99%
See 1 more Smart Citation